Social research. - New School for Social Research. Graduate Faculty of Political and Social Science ([New York, Graduate Faculty of Political and Social Science, New School for Social Research], 1934)
Includes section "Book reviews and notes."
"An international quarterly of the social sciences."
Index of economic articles in journals and collective volumes
Journal of economic literature
Social sciences index
ABC pol sci
America, history and life
Keywords: Social sciences -- Periodicals